2001
DOI: 10.1097/00008571-200107000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the CYP2D6*29 allele commonly present in a black Tanzanian population causing reduced catalytic activity

Abstract: Debrisoquine metabolism among Tanzanians has been found to be slower than expected from the CYP2D6 genotype. In order to evaluate any genetic explanation, the coding sequence and intron-exon boundaries of the CYP2D6 gene from three Black Tanzanian volunteers with a CYP2D6*1/*1 or CYP2D6*2/*2 genotype and debrisoquine metabolic ratios (MRs) > 1 were fully sequenced to screen for new mutations. Two functional mutations, G1747 to A (causing V136I) and G3271 to A (causing V338M), were identified in the CYP2D6*2/*2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 35 publications
9
62
0
Order By: Relevance
“…Variant CYP2D6.10 exhibited only approximately 10% of the activity of the wildtype protein. These data are in accordance with most of the previously reported results [15][16][17] and thus indicate that our CYP expression and metabolic activity analysis system is suitable for analysing the catalytic activities of the other CYP2D6 allelic variants. As shown in fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Variant CYP2D6.10 exhibited only approximately 10% of the activity of the wildtype protein. These data are in accordance with most of the previously reported results [15][16][17] and thus indicate that our CYP expression and metabolic activity analysis system is suitable for analysing the catalytic activities of the other CYP2D6 allelic variants. As shown in fig.…”
Section: Resultssupporting
confidence: 92%
“…In the present study, we successfully expressed wild-type and 24 allelic variants of CYP2D6 proteins in 293FT cells and characterized their enzymatic activities towards two typical CYP2D6-catabolized drugs. Regarding the typical allelic variants CYP2D6.2 and CYP2D6.10, our data strongly accord with the majority of the previously reported results [15][16][17], although we have not provided the kinetic parameters of these variants. Similarly, previous reports have been revealed that the results obtained for another CYP member, CYP2C9, also are in well agreement with those from other expression systems [13]; thus, data of the present study might be constructive for the functional prediction of these newly found CYP2D6 variants.…”
Section: Resultssupporting
confidence: 90%
“…Indeed, the emphasis of this review has been on drug efficacy and agent selection. However, there is significant evidence supporting variants predicting adverse events including the hyperuricemia of thiazide use 94 , bradycardia associated with β-blockers [5][6][7][8]95,96 , and ACEI-related cough 97 .…”
Section: Methodsmentioning
confidence: 99%
“…This creates an altered substrate specificity, 33 which is evident in vitro 33 but also when subjects of the CYP2D6*17 genotype are phenotyped in vivo. 34,35 In general, the activity of the CYP2D6.17 enzyme is lower than the wild-type enzyme.…”
Section: Cyp2d6 Genetic Polymorphismmentioning
confidence: 99%